2023
DOI: 10.1002/zaac.202300006
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Free Transfer C−H Borylation of Substituted Thiophenes

Abstract: Thiophenes are crucial chemical building blocks in the fields of medicinal and material chemistry. As such, the CÀ H functionalization of these units is of key importance for developing novel applications. Herein, we report the CÀ H borylation of thiophenes using metal-free transfer CÀ H borylation. When performed on C2-substituted thiophenes, the reaction is selective for the borylation on C5, while C3-substituted thiophenes are borylated on C2, a complementary selectivity from reported CÀ H borylation approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Furthermore, there is an urgent need to explore more convenient, metal-free, and environmentally sustainable methods for synthesizing sulfonamides and phosphoramidates. These innovative approaches, supported by reliable references, emphasize the increasing significance and widespread adoption of metal-free C–H activation techniques, solidifying their pivotal role as transformative tools in contemporary synthesis, 45–48,181 alongside the ongoing development of improved catalysts, reaction conditions, and solvent systems. 181…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there is an urgent need to explore more convenient, metal-free, and environmentally sustainable methods for synthesizing sulfonamides and phosphoramidates. These innovative approaches, supported by reliable references, emphasize the increasing significance and widespread adoption of metal-free C–H activation techniques, solidifying their pivotal role as transformative tools in contemporary synthesis, 45–48,181 alongside the ongoing development of improved catalysts, reaction conditions, and solvent systems. 181…”
Section: Discussionmentioning
confidence: 99%
“…45,46 These metal free approaches, supported by authoritative references, highlight the growing importance and widespread adoption of metal-free C–H activation techniques, solidifying their role as game-changing tools in modern synthesis. 47,48 The shift away from metal-based catalysts, while not entirely unprecedented, has gained substantial momentum due to its distinct advantages, including addressing heavy metal contamination issues, enhancing selectivity, and reducing environmental impact. This shift has also prompted a reevaluation of the traditional definition of “C–H activation” as it encompasses new mechanistic pathways and reactivity profiles.…”
Section: Factors Affecting C–h Aminationmentioning
confidence: 99%
“…The bifunctional nature of L is crucial as it introduces a basic site proximal to the electrophilic boron center (thus is a preorganized FLP). This facilitates C–H borylation via a six-membered transition state ( TS1 , Scheme ) which is calculated to be the highest energy state in the process . The concerted nature of C–B formation/C–H deprotonation enabled by bifunctional bases has proved essential to expand the scope beyond that using monofunctional bases and CatBH.…”
Section: Approach (I) Arene C–h Functionalization By Electrophiles De...mentioning
confidence: 99%
“…Moving beyond monofunctional bases in [CatB–L] 1+/0 systems, bifunctional derivatives, e.g., 2-DMAP, also have been explored. While this was initially in stoichiometric C–H borylation, later work with compound 5 (Scheme ) and more recently compounds such as 6 have shown that combining bifunctional bases with CatBH can expand the scope in catalytic electrophilic borylation to some degree . Chelation of bases such as 2-DMAP to {CatB} is disfavored as chelation would form a strained four-membered boracycle (Scheme , top) .…”
Section: Approach (I) Arene C–h Functionalization By Electrophiles De...mentioning
confidence: 99%
See 1 more Smart Citation